Islamic education in Uganda: challenges and prospects of Islamization of Knowledge. - Lujja, Sulaiman; Mohammed, Mustafa Omar; Hassan, Rusni (Minda Masagi Press and UIN SGD Bandung, West Java, Indonesia, 2016)
This paper is intended to assess the performance of the prevailing Islamic education in Uganda and how Islamization of human acquired knowledge can ϔigure into improvement of the performance of this curriculum to foster modernity. The study also avails a successful methodology towards Islamization of knowledge in the context of Ugandan education system. The study was conducted qualitatively using secondary data, i.e. information was collected using library search, where books, journal articles, periodicals, and online resources were used in gathering data. As it was the case in the ancient Islamic empire during its golden age, what will make Islamic education in Uganda strong is its openness to both Islamic studies and social sciences side-by-side in the same curriculum to complement each other in nurturing balanced graduates, who are well integrated intellectually and spiritually. While the Islamic traditional system of education does not provide solutions to most of the contemporary issues; the Western system of education will provide some solutions to these issues, but with contradictory worldview to that of Islam. Few studies have considered the Islamization of knowledge project in overcoming secularism in education and the prevalent challenges in Islamic education system across the Muslim world. This study employs the Islamization of knowledge project to counteract Muslim education problems in Uganda. It, therefore, makes a theoretical contribution by considering a new concept in education as a vehicle to revamp Islamic education in Uganda. KEY WORDS: Islam, education, Islamic education, Islamization of knowledge, and Uganda.